Evaluation of different newer insecticides against mango hopper (Bangladesh Journal of Agricultural Research, 2026)
The experiment was conducted during 2022-23 mango cropping season at Lac Research Station, Bangladesh Agricultultural Research Institute (BARI), Chapainawabganj to evaluate some newer insecticides against mango hopper, Idioscopus spp. (Hemiptera: Cicadellidae). The experiment was laid out in a randomized complete block design (RCBD) with three replications. The treatments comprised 12 treatments, viz. Chlorpyriphos+Cypermethrin 55 EC @ 1 ml/L of water, Cypermethrin 10 EC @ 1 ml/L of water, Diafenthiuron 50 EC @ 1.2 ml/L of water, Chlorpyriphos+Beta-cypermethrin 60 EC @ 1 ml/L of water, Lambda-Cyhalothrin 2.5 EC @ 1 ml/L of water, Monomihypo+Imidacloprid 80 WG @ 0.5 g/L of water, Nitenpyram+Pymetrozine 80 WDG @ 0.5 g/L of water, Imidacloprid+Lambda-Cyhalothrin 20 SC @ 0.5 ml/L of water, Indoxacarb+Emamectin Benzoate 25 WDG @ 0.1 g/L of water, Cartap+Acetamiprid 95 SP @ 1.5 g/L of water, imidacloprid 20 SL @ 0.5 ml/L of water and an untreated control. Each insecticide was sprayed twice, the 1st spray at 10 days of flowering and the second in 30 days after the 1st spray. All insecticidal treatments were found superior over untreated control for the management of mango hopper. Spraying Imidacloprid 20 SL @ 0.5 ml/L of water was found the most effective for the management of mango hopper, which offered the highest reduction (83.12% and 69.89%, after the first and second spray, respectively) of mango hopper population over control. This treatment also offered the highest fruit retention (100.22%, 56.2% and 101.09% at pea, marble and mature stages of fruit development, respectively) over control. Spraying Imidacloprid+Lambda-Cyhalothrin @ 0.5 ml/L of water offered the second highest efficacy both in terms of pest population reduction and fruit retention over control.Bangladesh J. Agril. Res. 49(1): 91-98, March 2024